A conspectus of constitutional challenges associated with the dismissal of employees for social media-related misconduct in the South African workplace - Howard Chitimira; Kefilwe Lekopanye (Revista Direito GV)
Abstract Currently, there is no legislation that specifically outlaws the misuse of social media in the South African workplace. Consequently, the absence of a robust social media legislation has culminated into several unlawful and unconstitutional dismissals of employees for social media-related misconduct in the South African workplace. Conversely, this gap has also given rise to rampant abuse of social media platforms by employees in the South African workplace. This status quo has caused various constitutional and other related challenges to be experienced by both employees and employers in South Africa. For instance, the abuse of social media by employees in the workplace during working hours could affect the reputation, productivity, and profitability of their employer’s business. Similarly, any employers’ draconian rules prohibiting or monitoring the use of social-media in the workplace could infringe upon their employees’ rights to freedom of expression, privacy, dignity and freedom of association. Accordingly, the article discusses constitutional challenges that could result from the unlawful dismissal of employees for social media-related misconduct in the South African workplace. In this regard, the article exposes challenges that occur when balancing the employees’ constitutional rights and the employers’ business reputation and related rights. This is done to isolate constitutional problems that ensue from the abuse of social media by employees in the workplace during office working hours. The article also discusses constitutional and related problems that stem from the unlawful dismissals of employees for social media-related misconduct in the South African workplace. Lastly, recommendations that could be adopted to combat employees’ social media-related misconduct and enhance the regulation of social media in the South African workplace are provided.